Crystal structure of SARS-CoV-2 Orf9b in complex with human TOM70 suggests unusual virus-host interactions - Xiaopan Gao; Kaixiang Zhu; Bo Qin; Vincent Olieric; Meitian Wang; Sheng Cui (Nature Communications, 2021)
SARS-CoV-2 orf9b binds to the mitochondrial outer membrane protein TOM70 and has been linked to the suppression of interferon responses. Here, the authors characterize the interactions of SARS-CoV-2 orf9b and human TOM70 biochemically, and they determine the 2.2 Å crystal structure of the TOM70 cytosolic domain with a bound SARS-CoV-2 orf9b peptide.